1998
DOI: 10.1088/0953-8984/10/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of possible 3d `heavy-fermion' compound

Abstract: Recent transport, specific heat and magnetization measurements indicated that the Heusler-type compound is a candidate for a 3d heavy-fermion system. As a first step towards a detailed theoretical understanding of the observed anomalous electronic properties of this compound, we have performed first-principles electronic structure and total energy calculations for and . The calculated lattice constants and magnetic moments are in good agreement with experiments. Remarkably, we find that, unlike , Heusler-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
117
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 24 publications
17
117
0
Order By: Relevance
“…The calculated DOS at the Fermi energy for the undoped system is 0.27 eV −1 /f.u. This gives a γ value for the linear heat capacity of 0.63 mJ mol −1 K −2 , nearly the same as 0.69 mJ mol −1 K −2 reported by Guo et al 8 The small difference between the two theoretical values is due to the different lattice constants and different methods used. However, both these values are order of magnitude smaller than the experimentally measured low-T γ value of 14 mJ mol −1 K −2 .…”
Section: Resultssupporting
confidence: 81%
“…The calculated DOS at the Fermi energy for the undoped system is 0.27 eV −1 /f.u. This gives a γ value for the linear heat capacity of 0.63 mJ mol −1 K −2 , nearly the same as 0.69 mJ mol −1 K −2 reported by Guo et al 8 The small difference between the two theoretical values is due to the different lattice constants and different methods used. However, both these values are order of magnitude smaller than the experimentally measured low-T γ value of 14 mJ mol −1 K −2 .…”
Section: Resultssupporting
confidence: 81%
“…In particular, the anomalous low temperature specific heat has been attributed to ferromagnetic clusters with a density of 0.003-0.004/unit cell, consistent with the results from NMR experiments. These works, as well, are in broad agreement with the results from band structure calculations, which predict that via Fe/V site exchange or crystallographic superstructure formation ferromagnetic clusters or long-range order might be generated in Fe 2 VAl [6][7][8]. Recently, it has been claimed that such impurity induced ferromagnetism was observed in the related Heusler compound Fe 2 TiSn [12].…”
supporting
confidence: 85%
“…For x = 1, that is for Fe 2 VAl, this leads to a fully ordered Heusler lattice, with Fe, V and Al each occupying separate cubic sublattices. Band structure calculations [6][7][8] indicated that in Fe 2 VAl each Fe ion occupying an Fe I site carries a magnetic moment. This requires a site exchange of V with an Fe II ion, which might cause, either via superstructure formation (i.e., V occupying exclusively one Fe II site) or a sufficiently large level of random Fe II/V site exchanges, a magnetically ordered state or anomalous behaviour from diluted magnetic clusters.…”
Section: )mentioning
confidence: 99%
“…6,8 Stimulated by these findings, theoretical work claimed Fe 2 VAl is a nonmagnetic semimetal with the pseudogap at the Fermi level. [15][16][17] The considerable mass enhancement of the conduction carriers was attributed to excitonic correlations 16 or spin fluctuations. 17 However, subsequent specific heat, C͑T͒, measurements in applied magnetic fields showed that the upturn in C / T at low temperatures results from a Schottky contribution of magnetic clusters in Fe 2 VAl.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The considerable mass enhancement of the conduction carriers was attributed to excitonic correlations 16 or spin fluctuations. 17 However, subsequent specific heat, C͑T͒, measurements in applied magnetic fields showed that the upturn in C / T at low temperatures results from a Schottky contribution of magnetic clusters in Fe 2 VAl. 8 The effects of off-stoichiometry have not been investigated quantitatively in the framework of nearly and weak ferromagnetism at x Ϸ 0 and ␦ Ϸ 0 yet.…”
Section: Introductionmentioning
confidence: 99%